Chemical insights into electrophilic fluorination of SnO2 for photoelectrochemical applications. Issue 35 (27th July 2021) - Bahuguna, Gaurav; Verma, Mohit; Gupta, Ritu
Abstract : A novel method for fluorination of SnO2 is developed that passivates oxygen defects and increases its electrical conductivity drastically, leading to enhanced charge transport in photoelectrochemical applications. Abstract : Recently, there has been substantial interest in the fluorination of nanomaterials-based thin films used in various optoelectronic devices for optimum charge transport across semiconducting layers. The discovery of electrophilic fluorinating agents such as Selectfluor® (F-TEDA) has led to the development of novel methods for fluorination of metal oxides such as tin oxide (SnO2 ) in this work. Herein, we elucidate the fluorination of SnO2 thin films using X-ray photoelectron spectroscopy (XPS) depth profiling. The interaction of the F-TEDA molecule with the SnO2 surface occurs via N–F bonds. Fluorine is found to occupy interstices and substitutional sites in the SnO2 lattice. The interstitial fluorine (1.21 at%) decays off by a depth of 61 nm in the SnO2 film. The substitutional fluorine (1.28 at%) in SnO2 results in remarkable changes in its electronic structure due to the lowering of oxygen defects by ∼80%. The electrical properties of the F–SnO2 film is examined by impedance spectroscopy analysis. F–SnO2 exhibits an increase in electrical conductivity by ∼1–2 orders of magnitude and an increase in electron density by ∼65%, making it suitable as a charge transport layer in photoelectrochemical cells (PECs). The PEC in aqueous medium at neutral pH with F–SnO2 as the charge transport layer shows ∼81% increase in the photocurrent density (at 1.6 V versus RHE) and decrease in charge transfer resistance by ∼36%. Thus, the efficient transport of photogenerated charge carriers is observed in PECs with minimal recombination losses for the fluorinated SnO2 films. This study helps in understanding the role of defect passivation via single-step fluorination of metal-oxide for charge transport layers which can be extended to perovskite solar cells in the future.